Pengaruh Pemberian Pilates Excercise terhadap Fleksibilitas Otot Hamstring pada Pemain Bola - Ratnasari, Rodyta, Wijianto S.St.FT., M.OR (2017)
Background: In the sport of football takes several components that support the quality and achievements of its players. One is the Hamstring muscle flexibility so as to reduce the level of injury to the players. This can be improved by using Pilates exercise. Objective: To determine the effect of Pilates exercise to the flexibility of the hamstring muscle in a football player. Benefits: Hamstring muscles to increase the flexibility of soccer players using the Pilates exercise. Method: This type of study is a quasi-experimental research, design Two group pretest-posttest design. The number of samples in this study of 22 samples. Samples were given treatment Pilates exercise method for the treatment and core stability exercise for the control group, did during the 4-week frequency of exercise three times a week. Statistical analysis using the Wilcoxon test to test the influence and Mann - Whitney Test to test different influences. Measuring tools Sit and Reach Test for flexibility in the muscles and limbs Leg Dynamometer for MMT. Result: After Wilcoxon Test No effect of Pilates exercise of the flexibility of the hamstring muscles with a p-value of 0.03. There is a difference between the effect of core stability exercise with Pilates method of exercise with core stability exercise the flexibility of the hamstring muscles after Mann - Whitney Test p-value of 0.000 was obtained. Conclusion: There is the effect of the Pilates exercises to the flexibility of the hamstring muscle in a football player.